2021
DOI: 10.1089/omi.2021.0080
|View full text |Cite
|
Sign up to set email alerts
|

Broadening COVID-19 Interventions to Drug Innovation: Neprilysin Pathway as a Friend, Foe, or Promising Molecular Target?

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus is anticipated to transition to an endemic state as vaccines are providing relief in some, but not all, countries. Drug discovery for COVID-19 can offer another tool in the fight against the pandemic. Additionally, COVID-19 impacts multiple organs that call for a systems medicine approach to planetary health and therapeutics innovation. In this context, innovation for drugs that pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 107 publications
0
1
0
1
Order By: Relevance
“…Conversely, the mature neutrophil clusters had suppression of granule content genes, but distinct patterns of gene activation that were relatively low in the immature populations ( Figure 4C ). Clusters 2 and 8 displayed upregulation of MMP9, several S100A genes including S100A12, and MME (i.e., Neprilysin), which have been implicated in the pathogenesis of COVID-19 ( 37 , 38 ). Clusters 3, 5, and 6 had high levels of expression of regulatory genes for transcription and apoptosis ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the mature neutrophil clusters had suppression of granule content genes, but distinct patterns of gene activation that were relatively low in the immature populations ( Figure 4C ). Clusters 2 and 8 displayed upregulation of MMP9, several S100A genes including S100A12, and MME (i.e., Neprilysin), which have been implicated in the pathogenesis of COVID-19 ( 37 , 38 ). Clusters 3, 5, and 6 had high levels of expression of regulatory genes for transcription and apoptosis ( Figure 4C ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that NEP inhibitor sacubitril can inhibit further cleavage of angiotensin 1-7 [17], and therefore, may favor the preservation of angiotensin 1-7 [17]. Studies have shown the beneficial effects of sacubitril on the regulation of angiotensin 1-7 and the improvement of outcomes of COVID-19 disease [15,17,[95][96][97]. Thus, several clinical trials using neprilysin inhibitor sacubitril have been proposed for the treatment of COVID-19 for a multitargeted therapeutic approach [15,98].…”
Section: Extracellular Vesicles Neprilysin and Thimet Oligopeptidase ...mentioning
confidence: 99%
“…АПФ є ключовою кініназою ІІ, яка відщеплює С-кінцеві дипептиди від кінінів, що робить їх неактивними. Кініни розщеплюються по залишку внутрішнього фенілаланіну (Phe5 у БК) мембранозв'язаною нейтральною ендопептидазою (neutral endopeptidase, NEP) [23]. Таким чином, враховуючи цей консорціум перетравлюючих ферментів, тривалість перебування БK у циркуляції після його тимчасової активності відповідає лише кільком секундам [24].…”
Section: калікреїн-кінінова система та синтез брадикінінуunclassified